A new kind of chelating agent with low pH value applied in the TSV CMP slurry*Project supported by the Major National Science and Technology Special Projects (No. 2009ZX02308), the Fund Project of Hebei Provincial Department of Education, China (No. QN2014208), the Natural Science Foundation of Hebei Province, China (No. E2013202247), and the Colleges and Universities Scientific Research Project of Hebei Province, China (No. Z2014088). (December 2015) - Hong 洪, Jiao 姣; Liu 刘, Yuling 玉岭; Zhang 张, Baoguo 保国; Niu 牛, Xinhuan 新环; Han 韩, Liying 力英
Abstract: TSV (through silicon via) is an emerging technology, which can realize micromation compared with the conventional packaging and extend Moore's law. Chemical mechanical polishing (CMP) is one of the most important steps in the process of TSV manufacture, and it is an enabling technology to extend Moore's law in the past two decades. Low pressure, low abrasive and low pH value are the main requirements for copper interconnection. In this paper, the effect of different kinds of TSV slurry with FA/O II or FA/O IV type chelating agent on CMP are studied. All kinds of slurry used in this study are alkaline with no added inhibitors. From the experiment results, it can be seen that the copper removal rate and surface roughness achieved by using the FA/O IV type chelating agent with a low pH value is superior to using the FA/O II type chelating agent.